Effects of low seawater pH on the marine polychaete Platynereis dumerilii. Issue 1 (15th June 2015) - Wäge, Janine; Hardege, Jörg D.; Larsson, Tomas A.; Simakov, Oleg; Chapman, Emma C.; Arendt, Detlev; Rotchell, Jeanette M.
Graphical abstract: Highlights: Acid–base regulation genes were used to study low pH impacts in a polychaete. NHE expression was altered by low pH seawater exposure and differentially localised. Carbonic anhydrase and calmodulin expression were not impacted past 1 day post exposure. Abstract: An important priority for any organism is to maintain internal cellular homeostasis including acid–base balance. Yet, the molecular level impacts of changing environmental conditions, such as low pH, remain uncharacterised. Herein, we isolate partial Na + / H + exchangers ( NHE ), carbonic anhydrase ( CA ), and calmodulin ( CaM ) genes from a polychaete, Platynereis dumerilii and investigate their relative expression in acidified seawater conditions. mRNA expression of NHE was significantly down-regulated after 1 h and up-regulated after 7 days under low pH treatment (pH 7.8), indicating changes in acid–base transport. Furthermore, the localisation of NHE expression was also altered. A trend of down regulation in CA after 1 h was also observed, suggesting a shift in the CO2 and HCO3 − balance. No change in CaM expression was detected after 7 days exposure to acidified seawater. This study provides insight into the molecular level changes taking place following exposure to acidified seawater in a non-calcifying, ubiquitous, organism.